Competition between photochemical and biological degradation of dissolved organic matter from the cyanobacteria Microcystis aeruginosa. (20th April 2015) - Bittar, Thais B.; Vieira, Armando A. H.; Stubbins, Aron; Mopper, Kenneth
Abstract Extracellular and intracellular dissolved organic matter (E‐DOM and I‐DOM, respectively) produced in axenic cultures by the cosmopolitan cyanobacteria Microcystis aeruginosa were characterized, and photoreactivity, bioreactivity, and the effects of phototransformations on bioavailability of E‐DOM and I‐DOM were assessed in laboratory experiments. Chromophoric (CDOM) and fluorescent (FDOM) properties were analyzed by spectrophotometry, and chemical signatures were obtained by ultrahigh resolution Fourier transform ion cyclotron resonance mass spectrometry (FTICR‐MS). E‐DOM was more heterogeneous regarding optical characteristics as indicated by the presence of multiple CDOM peaks and the more even distribution of FDOM components, and had less absolute and relative numbers for molecular formulae containing nitrogen (N) than I‐DOM. E‐DOM was more photolabile, with greater photochemical removal of dissolved organic carbon (DOC), CDOM and FDOM, and exhibited more pronounced photochemical alterations in molecular formulae composition than I‐DOM. E‐DOM was less biolabile, with less biological removal of DOC, CDOM, and protein‐like fluorescent material, and supported lower rates of bacterial productivity than I‐DOM. Phototransformations reduced the bioavailability of E‐DOM and I‐DOM, as shown by lower bacterial productivity and longer DOC and CDOM half‐lives in bioassays with photoirradiated DOM in comparison to those with nonirradiated DOM. Analyses of CDOM, FDOM, and FTICR‐MS revealed that the decrease in bioavailability was caused primarily by photolysis of the biolabile DOM, indicating competition between photochemical and biological removal of cyanobacterial DOM. These results provided insights into mechanistic effects of independent and combined photochemical and biological degradation on M. aeruginosa‐derived DOM.